Effects of six-month supplementation with beta-hydroxy-beta-methylbutyrate, glutamine, and arginine on vascular endothelial function of older adults - Ellis, Amy (Eur J Clin Nutr, 2015)
BACKGROUND: Vascular endothelial function declines with advancing age, due in part to increased oxidative stress and inflammation, and this age-related vascular dysfunction has been identified as an independent risk factor for cardiovascular diseases (CVD). This double-blind, placebo-controlled trial investigated the effects of a dietary supplement containing β-hydroxy-β-methylbutyrate (HMB), glutamine, and arginine on endothelial-dependent vasodilation of older adults. SUBJECTS/METHODS: Thirty-one community-dwelling men and women aged 65-87 years were randomly assigned to two groups. The treatment group received two doses of the supplement daily (totaling 3g HMB, 14g glutamine, 14g arginine) for six months while the control group received an isocaloric placebo. At baseline and week 24, vascular endothelial function was measured by flow-mediated dilation of the brachial artery, and fasting blood samples were obtained to measure high-sensitivity C-reactive protein (hsCRP) and tumor necrosis factor-α (TNF-α). RESULTS: Paired samples t-tests revealed a 27% increase in flow-mediated dilation among the treatment group (p=0.003) while no change was observed in the placebo group (p=0.651). Repeated-measures ANOVA verified a significant time by group interaction (p=0.038). Although no significant changes were observed for hsCRP or TNF-α, a trend was observed for increasing hsCRP among the placebo group only (p=0.059). CONCLUSIONS: These results suggest that dietary supplementation of HMB, glutamine, and arginine may favorably impact vascular endothelial function in older adults. Additional studies are needed to elucidate whether reduced inflammation or other mechanisms may underlie the benefits of supplementation.